An assessment of the impact of e-government on service delivery in Zimbabwe’s public sector. The case of Home Affairs: department of the Zimbabwe Republic Police from period 2005 – 2015 - Magaya, Emelda (Midlands State University, 2019)
The study was an assessment on the impact of e-government on service delivery in the public sector. The focus of the research was on how e-government has helped improve the service delivered by the Zimbabwe Republic Police from period 2005- 2015 and its other benefits thereof still to be uncovered as the use of e-government becomes popular in the police force. In this case, the study triangulated the research methodology due to mixed perceptions concerning e-government as an effective tool to improve public service delivery. The research findings gave a clear manifestation of the potential of e-government to positively impact service delivery by promoting the principles of transparency, accountability and effectiveness. The research also uncovered the fact that the manual way of service delivery is being outdated by the improvements in technology and delivering service manually proves to give a fatal breeding ground for crime rates and corruption among the police force and members of the public. In this regard, the research proposes the need for the adoption of a clear and sound e-government system able to curb the inherent problems in the current situation. Along this line, e-government is touted to have a potential in creating public value thereby improving service delivery.